Efficacy Of Furosemide in the Management of Transient Tachypnoea of Newborn - Hafsa Arshad; Awais Tahir; Bilal Akhlaq; Umair Anees; Hafiz Abdul Quddus; Iqbal, Muhammad (Medical Journal of South Punjab, 2025)
Objective: To see the efficacy of intravenous Furosemide in the management of transient tachypnoea of newborn.Methodology: This study was conducted at the Department of Paediatrics, Fauji Foundation Hospital Rawalpindi from August to December 2024. Neonates with 34 to 40 weeks of gestation diagnosed with TTN and requiring CPAP to maintain oxygen saturation > 90% were included. Neonates born with congenital malformations, systemic infection, requiring mechanical ventilation and intubation were excluded. Intravenous furosemide was administered to Group A, while Group B was managed conservatively and normal saline as a placebo was used. Following the start of therapy each patient will be monitored to assess the efficacy of the therapy, in terms of length of hospital stay and duration of oxygen therapy.Results: One hundred and seventy-two (n=172) patients had a mean gestational age of 38.45±1.07 weeks. The respiratory rate at admission was 84.75±15.49 breaths/minute in Group A and 82.69±13.89 breaths/minute in Group B with no statistical difference (p=0.403). Post-intervention in Group A the respiratory rate was 46.61±4.97 breaths/minute and in Group B it was 51.24±4.27 breaths/minute (p